The Effect of Baby Massage on Sleep Quality of Baby Aged 1-3 Months - Sulfianti Sulfianti; Sakinah Amir; Sitti Asiah Yakub (Journal La Medihealtico, 2022)
Sleep quality is the quality or physiological state obtained during sleep. One way to improve sleep quality is baby massage. Baby massage is a touch therapy or direct contact with the body that can provide a feeling of security and comfort to the baby. This study aims to determine the effect of infant massage on the sleep quality of infants aged 1-3 months. This study used a quasi-experimental method with a one group pre test post test design. The sampling technique in this study was non-probability sampling with purposive sampling method. The results of this study indicate that there is an effect of infant massage on the sleep quality of infants aged 1-3 months in the working area of UPT Puskesmas Watampone, with the Wilcoxon test results obtained a significant number or probability value (0.001) much lower than the significant standard of 0.05 or (p < α), then H0 data is rejected and Ha is accepted, which means there is an effect of infant massage on the sleep quality of infants aged 1-3 months in the work area of the Task Implementation Unit (UPT) of the Watampone Health Center, Bone Regency.